2007
DOI: 10.1038/sj.hdy.6801083
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium analysis in the genetically isolated Norfolk Island population

Abstract: Norfolk Island is a human genetic isolate, possessing unique population characteristics that could be utilized for complex disease gene localization. Our intention was to evaluate the extent and strength of linkage disequilibrium (LD) in the Norfolk isolate by investigating markers within Xq13.3 and the NOS2A gene encoding the inducible nitric oxide synthase. A total of six microsatellite markers spanning B11 Mb were assessed on chromosome Xq13.3 in a group of 56 men from Norfolk Island. Additionally, three si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…A SOLAR LOD score of 3.0, 2.1, 1.2 and 0.59 equate to pointwise P values of 1×10 −4 , 1×10 −3 , 1×10 −2 , and 0.05, respectively. Previous studies of CVD risk determined the current trimmed pedigree structure had good power to detect the heritability of phenotypes whose variation is partially attributable to additive genetics and to detect loci for such phenotypes (Bellis et al, 2007). …”
Section: 1 Materials and Methodsmentioning
confidence: 99%
“…A SOLAR LOD score of 3.0, 2.1, 1.2 and 0.59 equate to pointwise P values of 1×10 −4 , 1×10 −3 , 1×10 −2 , and 0.05, respectively. Previous studies of CVD risk determined the current trimmed pedigree structure had good power to detect the heritability of phenotypes whose variation is partially attributable to additive genetics and to detect loci for such phenotypes (Bellis et al, 2007). …”
Section: 1 Materials and Methodsmentioning
confidence: 99%
“…Consistent with their isolated history, we recently showed that a set of individuals drawn from Norfolk Island show long stretches of linkage disequilibrium. 19 Further background information on the Norfolk Island data 20 and on Polynesian settlement more generally 21 was published earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Norfolk Island is a genetic isolate and has been targeted in previous genetic research into the aetiology of cardiovascular disease. [15][16][17] Using a similar approach, we are hoping to use this initial framework to uncover novel information about ocular phenotypes. Collectively, the population has been very supportive of health-related research.…”
mentioning
confidence: 99%